Utilização da flotação em coluna para o tratamento de efluente da indústria láctea - Vilar, Andréa Cavalcante (2009)
The main environmental impacts caused by the dairy industries are related to discharge of liquid effluents, usually without any kind of control or treatment. The dairy effluent is characterized by high content of organic matter, being important the implementation of techniques for its effective treatment and low cost. This study aims to evaluate the performance of a flotation column operating in batch for the pre-treatment of a dairy effluent. The first step was to investigate the processes of flocculation / sedimentation and flotation of a synthetic dairy effluent in the isoelectric point. This was prepared by the addition of milk powder to water under mechanical stirring, to obtain a homogeneous suspension. It was used a milk concentration of 6.5% (w/v), aiming simulate the characteristics of a real effluent. The optimal condition of flocculation was determined using a jar test by the addition of an aqueous solution of HCl 1:10 (v/v). Settling tests using the flocculated suspension were performed in duplicate through the observation of the displacement of flocs along the time. Flocs density was evaluated through centrifugal technique and the flocs diameter was determined according equations that describe the flocculent systems fluidodynamic. Flotation test was carried out in a column operating in batch. The optimal condition of flocculation was observed at pH 4.0, with a flocs recovery efficiency of 88% in the jar test. Settling tests showed that after 15 minutes flocs had already reached the compactation region, being observed a stabilization of the sediment height. Settling maximum velocity was similar for both experiments, with values of 0.97 cm/min and 0.84 cm/min. Density and flocs diameter were 1,016±0,012 g/cm3 and 275 mm, respectively, and the solids recovery efficiency was 93%, demonstrating the efficiency of the flocculation/sedimentation process for primary treatment of a flocculated synthetic dairy effluent. Moreover, flotation was not satisfactory, with a effluent sedimentation in the flotation column. In the second stage of work was used an industrial dairy effluent (obtained from cheese processing) from a small industry located in the agreste region of Pernambuco State. Physical-chemical characterization of effluent was made to determine the contents of protein, ash, lipids, carbohydrates and pH. The effluent had approximately 5 g/100mL carbohydrates, 0.8 g/100mL of proteins and lipids of 0.6 g/100mL and pH 5.0. The visual observation of flocs formation in the range pH 2,5 to pH 5,5 was not possible. A factorial design was used to evaluate the efficiency of the flotation column to remove the COD content, and the variables investigated were pH and air flow. The maximum removal of COD (70%) was achieved for an air flow of 1.362 mL/min, while pH was not statistically significant. Flotation efficiency reaches 76% in the presence of a flocculating agent in a concentration of 0.1%. The effluent showed low hydrophobicity, isoelectric point at pH 4.0 and mean particle diameter of 0.43mm. Experimental data were fitted satisfactorily to a first-order kinetic model